'Liquid running communities' – an analysis of serious runners' communities. Issue 3 (3rd July 2018) - Pedersen, Henrik; Kremmer Pedersen, Line; Thing, Lone Friis
Abstract: This study targets Serious Runners, who are redefining the term 'running community'. The main focus is to investigate how the Serious Runners engage with each other within the new running communities and what they experience by belonging to them. Inspiration is drawn from Bauman's 'liquid modernity and community' and abductive reasoning is used within the hermeneutical interpretation tradition and with a theory borne interpretation. In-depth interviews are conducted with runners from traditional and new urban running communities about their experiences of belonging. The results show that liquid modernity's 'peg' communities act as bridges between contradictory desires and particularly between the need for individuality and community. The runners experience a 'momentary' community when training with others or joining 'swarms' of runners during competitions. Serious Runners challenge the dichotomy of running alone vs. organized running in clubs. The study introduces a model that draws on new forms of liquid 'peg' communities and identifies new types of communities referred to as 'individualized running within communities' and 'jointly individualized running communities'. Further research is needed to better understand these new community types and to determine how activities could be organized to encourage their formation in the broader sports arena.